2024
DOI: 10.3390/s24051374
|View full text |Cite
|
Sign up to set email alerts
|

GY-SLAM: A Dense Semantic SLAM System for Plant Factory Transport Robots

Xiaolin Xie,
Yibo Qin,
Zhihong Zhang
et al.

Abstract: Simultaneous Localization and Mapping (SLAM), as one of the core technologies in intelligent robotics, has gained substantial attention in recent years. Addressing the limitations of SLAM systems in dynamic environments, this research proposes a system specifically designed for plant factory transportation environments, named GY-SLAM. GY-SLAM incorporates a lightweight target detection network, GY, based on YOLOv5, which utilizes GhostNet as the backbone network. This integration is further enhanced with Coord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Research has shown that incorporating attention mechanisms and introducing upsamplers [33][34][35][36] have been proven to effectively enhance model detection accuracy. Zeng et al [37] proposed a YOLOv8 model based on the CBAM mechanism, which can effectively select key features of targets, achieving high-precision recognition of coal and gangue.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that incorporating attention mechanisms and introducing upsamplers [33][34][35][36] have been proven to effectively enhance model detection accuracy. Zeng et al [37] proposed a YOLOv8 model based on the CBAM mechanism, which can effectively select key features of targets, achieving high-precision recognition of coal and gangue.…”
Section: Discussionmentioning
confidence: 99%